PENGARUH COLLATERALIZABLE ASSETS, FREE CASH FLOW, INVESTMENT OPPORTUNITY SET, LEVERAGE, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR SUBSEKTOR FARMASI - Wahyu Handayani (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
Dividend policy is the decision whether to distribute the profits generated by the company to shareholders in the form of dividends or to reserve capital to fund future investments. The independent variables in this study are Collateralizable Assets (CA), Free Cash Flow (FCF), Investment Opportunity Set (MVE/BVE), Leverage (DER), Profitability (ROA) while the dependent variable is dividend payout ratio (DPR). This type of research is quantitative research, and used secondary data. The sampling method is a saturated sample, and there are 10 companies that distribute dividends in a row during 2018-2020. The data analysis technique used is panel data regression. Data processing in this study uses the E-Views 9 program. The results show that the CA, FCF, DER, ROA variables have no effect on DPR while MVE/BVE has an effect on DPR.